FINANCIAL SECURITY OF ENTERPRISES IN THE DIGITAL ECONOMY - Mekhed, A.; Varnalii, Z. (Socio-economic relations in the digital society, 2021)
The aim of the article is to study the impact of digitalization on the activities of enterprises and the organization of their financial security, in particular to define financial security as a structural component of economic security in the context of this work, outline the benefits and problems, adapted to the conditions of the digital environment.The author’s definition of financial security as a measure of harmonization in time and space of economic interests of the enterprise with the interests of the environment in order to form an appropriate system to protect the financial interests of the enterprise from existing and potential internal and external threats. The essence of the digital economy as a new paradigm of economic and social development is studied, where the main factor of production is the information presented in digital form. The characteristic features of the digital economy, as well as the positive and negative aspects that affect the security of business structures are identified. The essence and role of the financial security system of the enterprise in the conditions of digitalization of economy are defined and the basic provisions of development of the financial security mechanism adapted to conditions of the digital environment.In the process of digital transformation, the format of manufactured products, approaches to the development and production of such products are changing, a new way of life is being formed, defined by new formats of business processes, digital products, digital markets, relationships between business entities, which creates the need to rethink approaches to security. enterprise and the adaptation of the financial security mechanism according to the requirements of the digital environment.At the same time, the results of the functioning of the mechanism of financial security of the enterprise in a digital economy include: ensuring sustainable development in changing conditions; increase positive cash flows; creation and use of modern IT systems and business models; formation of a high level of management and rapid response to threats. In turn, ensuring the financial security of the enterprise in a digital economy should be based on the following principles: systematic; prompt response to threats; continuity of activities; consistency of decisions and actions; the appropriateness of the cost of security measures; competence of management staff and employees of the company; consistency in carrying out activities; focus on results.
Keywords: financial security; digital economy; digitalization; digital technologies; digital transformation; financial security mechanism